The million-year evolution of the glacial trimline in the southernmost Ellsworth Mountains, Antarctica - Sugden, David; Hein, Andrew; Woodward, John; Marrero, Shasta; Rodés, Ángel; Dunning, Stuart; Stuart, Finlay; Freeman, Stewart; Winter, Kate; Westoby, Matt (Earth and Planetary Science Letters, 2017)
An elevated erosional trimline in the heart of West Antarctica in the Ellsworth Mountains tells of thicker ice in the past and represents an important yet ambiguous stage in the evolution of the Antarctic Ice Sheet. Here we analyse the geomorphology of massifs in the southernmost Heritage Range where the surfaces associated with the trimline are overlain by surficial deposits that have the potential to be dated through cosmogenic nuclide analysis. Analysis of 100 rock samples reveals that some clasts have been exposed on glacially moulded surfaces for 1.4 Ma and perhaps more than 3.5 Ma, while others reflect fluctuations in thickness during Quaternary glacial cycles. Modelling the age of the glacially moulded bedrock surface based on cosmogenic 10Be, 26Al and 21Ne concentrations from a depth-profile indicates a minimum exposure age of 2.1–2.6 Ma. We conclude that the glacially eroded surfaces adjacent to the trimline predate the Last Glacial Maximum and indeed the Quaternary. Since erosion was by warm-based ice near an ice-sheet upper margin, we suggest it first occurred during the early glaciations of Antarctica before the stepped cooling of the mid-Miocene at ∼14 Ma. This was a time when the interior Antarctic continent had summers warm enough for tundra vegetation to grow and for mountain glaciers to consist of ice at the pressure melting point. During these milder conditions, and subsequently, erosion of glacial troughs is likely to have lowered the ice-sheet surface in relation to the mountains. This means that the range of orbitally induced cyclic fluctuations in ice thickness have progressively been confined to lower elevations.